Les produits vendus au macellum - Ruyt, Claire De (Food & History, 2007)
Abstract The macellum, created at Rome at the end of 3th century BC, a part of the public market specialised in selling food products. A single building brought together ancient places used for the fish market (forum piscarium) and dedicated to the sales of meats, fowl, and pork. During the late Republic and Early Empire, this specialisation is attested by texts with insistance on fish sale, while, during the Late Empire, this building became more dedicated to sales of meats and the slaughtering of animals. If inscriptions identifying the macella of Roman world don’t enlighten us as to their functions, the equipment allows to guess them : meat and fish needed tables, basins, and fountains ; worship dedicated to Mercury and Neptune are often present. As for archeozoological remains, they must be clearly associated with occupations’ levels before being used as arguments for identifying of these buildings. Abstract Le macellum, créé à Rome vers la fin du 3e s. a. C., était un marché public spécialisé dans la vente de produits alimentaires. Un bâtiment unique réunit alors d’anciens lieux destinés au marché au poisson (forum piscarium) et aux ventes de viandes, volailles et charcuteries. Cette spécialisation est attestée par les textes, avec une insistance sur la vente du poisson durant la République tardive et le Haut Empire, tandis qu’à l’époque tardive, l’édifice est davantage orienté vers les ventes de viandes et l’abattage d’animaux. Si les inscriptions identifiant les macella du monde romain n’en éclairent pas les fonctions, leurs équipements permettent de les appréhender : viandes et poissons nécessitaient des tables, bassins et fontaines ; les cultes à Mercure ou Neptune sont souvent présents. Quant aux vestiges archéozoologiques, ils doivent être clairement associés aux niveaux d’occupation avant de servir d’argument d’identification de ces édifices.